2015
DOI: 10.1111/asj.12376
|View full text |Cite
|
Sign up to set email alerts
|

Diverse functions of perlecan in central nervous system cells in vitro

Abstract: Therapeutic treatment targeting one cell type is considered ineffective in remedying any injury to the central nervous system (CNS). Perlecan, a multi-functional, heparan sulfate proteoglycan, shows diverse effects on distinct cell types, suggesting that it is one of the candidates that can augment the regenerative mechanisms in the injured CNS. Therefore, we examined the functions of perlecan in CNS cells in vitro by using perlecan purified from bovine kidney. Perlecan-coated cell culture plates, unlike their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Additionally, perlecan surrounds axonal fascicle bundles from olfactory sensory neurons in embryonic mice (Shay et al, 2008 ). Perlecan can also promote neurite extension in vitro (Nakamura et al, 2015 ). In chick embryos, the expression pattern of this protein has been studied until HH17, where, as in the present report, perlecan becomes circumscribed to the external limiting membrane (Soulintzi and Zagris, 2007 ) and does not appear to participate in axon guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, perlecan surrounds axonal fascicle bundles from olfactory sensory neurons in embryonic mice (Shay et al, 2008 ). Perlecan can also promote neurite extension in vitro (Nakamura et al, 2015 ). In chick embryos, the expression pattern of this protein has been studied until HH17, where, as in the present report, perlecan becomes circumscribed to the external limiting membrane (Soulintzi and Zagris, 2007 ) and does not appear to participate in axon guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral testing took place prior to (baseline) MCAo surgery and on PSD 1,4,6,8,11,13,15,18, and 20. Mice were placed on the rotor-rod (San Diego Instruments) for 5 min with increasing acceleration (0-40 rpm, 3 trials) measuring total distance (cm).…”
Section: Behavioral Testingmentioning
confidence: 99%
“…Importantly, complete perlecan knockout is embryonic lethal, and mice have brain atrophy associated with reduced cell proliferation, hampered migration of developing neurons, and impaired neurogenesis [13,14]. Conversely, perlecan treatment promotes in vitro neural stem/progenitor cell proliferation and neuritogenesis [15]. Collectively, this suggests a key role of perlecan in developmental neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies by Nakamura et al ( 2015 ) demonstrated addition of exogenous perlecan to neural cultures promoted NSPC proliferation as well as neurite extension. Addition of heparin was found to promote NSPC proliferation, although this was not significant, suggesting perlecan as well as its associated GAGs are required.…”
Section: Hspgs and Neurogenesismentioning
confidence: 99%